PROGRAM PENYIAPAN DAN PEMBINAAN GURU BAHASA ARAB PROFESIONAL DI INDONESIA - Tamam, Asep M (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2014)
Professional Arabic teacher preparation program in Indonesia still faces various problems in its regulation and implementation, such as absence of the institution concerned and unavailability of qualified teachers applicant. This article explains how to prepare and develop professional Arabic teachers with integrated programs that will improve the quality of Arabic instruction in Indonesia. Additionally, the competence and professionalism of Indonesian Arabic teachers are increasing in the future. DOI: 10.15408/a.v1i1.1130